INTEGRATING AQUACULTURE AND HYDROPONICS: A REVIEW OF AQUAPONICS SYSTEMS AND THEIR SUSTAINABILITY - Puspa RC; Janak Singh Rawal (Engineering Heritage Journal)
Integrating hydroponics and aquaculture into a single system, aquaponics can be an effective strategy that fight against regional and global issues like food scarcity, soil erosion, climate change, and population growth. This review focuses on how aquaponics can enhance food production and resource utilization based on the subject’s theoretical principles, the type of systems, and sustainability aspects. Hydroponics or aquaculture, which is the production of plants without soil and the farming of water animals respectively are examined in respect of their enhancing benefits in aquaponic systems. The benefits and drawbacks of each important system design are analyzed: Nutrient film technique (NFT), deep-water culture (DWC), and media-based grow beds (MGB). Thus, though NFT systems provided the lowest nitrate removal efficiency and overall lettuce yields, these systems were preferred by the users because of their cheap and rather simplistic construction. At the same time, MGB systems offered stability and were adequate for relatively small-scale projects, but required constant care and attention. Aquaponics Systems required large structures, but were extremely water conserving and low-profile. Each system has been estimated in terms of performance, easy to use, and maintenance. Nitrifying bacteria, plants, and fish share mutual interactions that help in water purifying the nutrient cycling process. Nutrients are used by plants to grow, which cleans the water. The purified water is immediately cycled again into the fish tank, ensuring that the scientific basis of aquaponics is followed to in all systems. This review also looks at the economic feasibility of aquaponics and limitation before concluding that it is a sustainable means of carrying out agriculture and it highlights the opportunity of using aquaponics for sustainable food production and environment preservation.